2002
DOI: 10.1037/0893-3200.16.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Marital quality, coping with conflict, marital complaints, and affection in couples with a depressed wife.

Abstract: This study compared three groups of women--outpatient depressed, inpatient depressed, and community control--and their husbands on a range of variables including marital functioning and styles of coping with conflict. Outpatient depressed couples reported greater marital distress and more destructive and less constructive tactics for resolving conflict than did community control couples. They also were more likely to have been previously married and to express regrets about having married their current husband… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
122
2
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(138 citation statements)
references
References 50 publications
8
122
2
6
Order By: Relevance
“…In contrast, the interpersonal conflict literature has often conceptualized behavioral reactions as constructive, destructive, and avoidant (Acitelli, Douvan, & Veroff, 1993;Canary, Cunningham, & Cody, 1988;Coyne, Thompson, & Palmer, 2002;Fingerman, 1998;Noller & Feeney, 1998). Constructive behaviors are active and beneficial for the relationship, such as compromising, calm discussion, and listening.…”
Section: Age and Reactivity To Interpersonal Tensionsmentioning
confidence: 99%
“…In contrast, the interpersonal conflict literature has often conceptualized behavioral reactions as constructive, destructive, and avoidant (Acitelli, Douvan, & Veroff, 1993;Canary, Cunningham, & Cody, 1988;Coyne, Thompson, & Palmer, 2002;Fingerman, 1998;Noller & Feeney, 1998). Constructive behaviors are active and beneficial for the relationship, such as compromising, calm discussion, and listening.…”
Section: Age and Reactivity To Interpersonal Tensionsmentioning
confidence: 99%
“…For example, partner effects have been studied to evaluate the perspective that there are burdens associated with being in a relationship with someone with mental health problems and that these burdens may result in lower relationship satisfaction for the partner (e.g., Chakrabarti, Kulhara, & Verma, 1993;Coyne et al, 1987). Results from prior studies have found that the presence of psychopathology in one person is associated with lower marital satisfaction in the partner (e.g., Bauserman et al, 1995;Coyne, Thompson, & Palmer, 2002;O'Farrell & Birchler, 1987).…”
mentioning
confidence: 99%
“…The findings are similar to study by Coyne JC et al which revealed that there were decreased expression of affection and excess marital complaints in either gender of depressed patients. 21 Decision making plays important role in marital quality. As per view of male partner, marital quality is good when they have more decision making power than their wives and vice versa.…”
Section: Discussionmentioning
confidence: 99%